2016
DOI: 10.1155/2016/2905789
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Tobacco Smoking on Retinal and Choroidal Thickness in Greek Population

Abstract: Aim. To investigate the effect of more than 25-year cigarette smoking on choroidal and retinal thickness, using spectral domain optical coherence tomography (SD-OCT). Methods. Thirty-one smokers and 25 age- and sex-matched nonsmokers, serving as control group, were submitted to slit-lamp biomicroscopy and dilated fundoscopy, SD-OCT, measurements of intraocular pressure (IOP), central corneal thickness (CCT), and axial length (AL). Heidelberg Spectralis was used to calculate choroidal thickness (CT), ganglion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 33 publications
4
40
4
3
Order By: Relevance
“…In our study, there was no significant difference in retinal thickness at the fovea between smokers and the control group. This result was consistent with previous reports in which smoking did not appear to affect retinal thickness in the healthy population, 11,13,14 although certain layers within the retina could be thinner in smokers, such as the ganglion cell complex layer 14 and retinal nerve fiber layer. 39 Interestingly, in our subgroup analysis, those who smoked 8 to 12 pack-years had higher FRT compared to controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, there was no significant difference in retinal thickness at the fovea between smokers and the control group. This result was consistent with previous reports in which smoking did not appear to affect retinal thickness in the healthy population, 11,13,14 although certain layers within the retina could be thinner in smokers, such as the ganglion cell complex layer 14 and retinal nerve fiber layer. 39 Interestingly, in our subgroup analysis, those who smoked 8 to 12 pack-years had higher FRT compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…11 Regarding chronic effects of smoking, decreased CT were more often observed in chronic smokers. 12,14 However, there was one report that showed no significant difference in CT between smokers and non-smokers. 13 This discrepancy can also be due to the fact that CT being a single dimension measurement may result in possible inherent variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Our results showed that GCC measurements of chronic smokers were much lower than that of non-smokers. This was in accordance with the outcomes reported by Moschos et al 20 who demonstrated thinner GCC thickness in smokers. We also found that GCC thickness was more reduced in males than females (p=0.005).…”
Section: Figuresupporting
confidence: 93%
“…Choroidal thickness is affected by gender, age, systemic diseases such as hypertension, axial length of the eye, systemic drugs such as phosphodiesterase 5 inhibitors and intraocular pressure. [15][16][17][18][19] Kantarci et al 16 compared macular and choroidal thicknesses between healthy individuals and long-term smokers who had been smoking for at least 20 years, and similar results were attained. In another study by Dervişo gulları et al, 17 difference between smokers and control subjects in retinal and choroidal thickness was found to be insignificant.…”
Section: Discussionmentioning
confidence: 86%